Tunable optical vortex from a nanogroove-structured optofluidic microlaser - Qiao, Zhen (2022)
Optical vortices with tunable properties in multiple dimensions are highly desirable in modern photonics, particularly for broadly tunable wavelengths and topological charges at the micrometer scale. Compared to solid-state approaches, here we demonstrate tunable optical vortices through the fusion of optofluidics and vortex beams in which the handedness, topological charges, and lasing wavelengths could be fully adjusted and dynamically controlled. Nanogroove structures inscribed in Fabry-Pérot optofluidic microcavities were proposed to generate optical vortices by converting Hermite-Gaussian laser modes. Topological charges could be controlled by tuning the lengths of the nanogroove structures. Vortex laser beams spanning a wide spectral band (430-630 nm) were achieved by alternating different liquid gain materials. Finally, dynamic switching of vortex laser wavelengths in real-time was realized through an optofluidic vortex microlaser device. The findings provide a robust yet flexible approach for generating on-chip vortex sources with multiple dimensions, high tunability, and reconfigurability.